Different Effects of Clopidogrel and Clarithromycin on the Enantioselective Pharmacokinetics of Sibutramine and its Active Metabolites in Healthy Subjects1. (4th February 2013) - Shinde, Dhananjay D.; Kim, Ho‐Sook; Choi, Jae‐Seok; Pan, Wei; Bae, Soo Kyung; Yeo, Chang‐Woo; Shon, Ji‐Hong; Kim, Dong‐Hyun; Shin, Jae Gook
Abstract In this study, we assessed the effects of clopidogrel and clarithromycin, known CYP2B6 and CYP3A inhibitors, respectively, on the enantioselective disposition of racemic sibutramine in conjunction with CYP2B6 polymorphisms in humans. Sibutramine showed enantioselective plasma profiles with consistently higher concentrations of R‐enantiomers. Clopidogrel and clarithromycin significantly increased the sibutramine plasma concentration, but their effects differed between enantiomers; a 2.2‐fold versus 4.1‐fold increase in the AUC in S‐enantiomer and 1.8‐fold versus 2.0‐fold for the R‐enantiomer, respectively. The AUCs of S‐ and R‐desmethyl metabolites changed significantly during the clopidogrel phase (P < .001 and P < .001, respectively) but not during the clarithromycin phase (P = .099 and P = .090, respectively). Exposure to sibutramine was higher in subjects with the CYP2B6*6/*6 genotype, but no statistical difference was observed among the CYP2B6 genotypes. These results suggest that the enantioselective disposition of sibutramine and its active metabolites are influenced by the altered genetic and environmental factors of CYP2B6 and CYP3A activity in vivo.